The Effect of Post-Placental Intrauterine Contraceptive Devices on Decreasing in Uterine Fundus Height in Postpartum SC Mothers - Tutuk Yuliyanti; Juda Julia Kristiarini; Bima Suryantara (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Contraception and family planning services are an essential part of reproductive health. Postpartum IUDs in SC postpartum have a much lower expulsion rate than vaginal delivery. Objective: to determine the effect of post-placental intrauterine devices on the decrease in fundus uteri. Methods: Using a correlational analytical research design, the research design used is a prospective cohort with a sample size of 30 for the treatment group and 30 for the control group. Result: It can be concluded that the effect 2 hours after the installation of post-placental IUD is known (p-value = 0.279), which indicates that there is no influence between the variable of post-placental IUD installation of SC delivery mothers and the decrease in fundus uteri height. The effect of post-placental IUD insertion on the decrease in fundus uteri height in SC postpartum mothers at Karanganyar Regional Hospital on day 3 shows a p-value of 0.262, and it shows that there is no influence between the variable post-placental IUD insertion of SC mothers and the decrease in fundus uteri height. On day 7, the p-value = 0.008 means that the p-value is smaller than the value of α = 0.05 (p-value < 0.05) and that there is an influence between the variable of post-placental IUD insertion of SC mothers and the decrease in fundus uteri height. Post-placental IUD is a reference for making birth control choices during the postpartum period without interfering with breast milk. Conclusion: The conclusion does not prove the hypothesis in part because the rapid effect on the decrease in TFU in SC postpartum mothers is only after 7 days from the insertion of the IUD, while at 2 hours of IUD insertion and day 3 of IUD insertion does not have a rapid effect on reducing TFU in SC postpartum mothers. implications for the management of maternity women who plan to postpone the next pregnancy and this research can be used as empirical evidence, that a post-placental intrauterine device acceptor has the potential to increase uterine contractions, accelerate the decrease in fundus uteri height on day 7.